Utilisation of remote sensing and geographic information system for compiling of agricultural land resources database in sragen regency. Issue 1 (March 2021) - Utomowati, R; Ahmad,; Suryanto,
Abstract: Availability of accurate information on agricultural land resources in Indonesia is important. An alternative method is needed to provide agricultural resource information quickly and accurately. The use of remote sensing and Geographic Information Systems (GIS) is expected to be an alternative method as a basis for compiling a database of agricultural information resources, specifically carrying capacity of agricultural land. Availability of a database of carrying capacity of agricultural land is important, to realise sustainable development, spatial planning must be based on environmental carrying capacity. The research objectives are (1). Compile the database for carrying capacity in Sragen Regency (2). Analysing the utilisation of remote sensing and GIS as the basis for compiling a database of carrying capacity for agricultural land in Sragen Regency. The main data source of the research is satellite imagery. Data collection methods used are image interpretation, field observations, interviews, and documentation. The research approach is used spatial description. The results of the study are: (1) The compilation of a database of land carrying capacity of Sragen Regency (2). Remote sensing satellite imagery and GIS can be used as the basis for compiling the database for the carrying capacity of the agricultural land in Sragen Regency.